Interoperability between Bluetooth and WiFi networks - Cervantes, Ma Margarita; Hong, Kathryn Joyce; Ramos, Faye Marian (2007)
Mobile devices nowadays come with at least one technology that allows them to communicate with other devices. Among such technologies are Bluetooth (IEEE 802.15), Wireless LAN (IEEE 802.11, also known as WiFi), Infrared and GPRS. Different mobile devices are usually equipped with at least any one of these, and thus, communicating with another device equipped with a different connectivity technology presents a problem. In this study, the group has created a system that alows mobile devices equipped with either Bluetooth or WiFi to interoperate, or in simpler terms, to communicate with each other, despite the apparent differences in their respective protocols and other characteristics. The implementation consists of modules for packet and protocol translation. The system was implemented on laptops and mobile phones and tested by deploying a client-server multicast chat application with file transfer on top of the interoperation modules. The platforms used are Java 2 Standard Edition and Java 2 Micro Edition.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Bluetooth technology; Wireless communication systems; Wireless LANs; IEEE 802.11 (Standard).